(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Background: It is important to use objective methods for assessing intraocular inflammation in the practical management of uveitis. Previously, we have found that, on day 1 of unilaterally induced non-infectious anterior and intermediate uveitis in rabbits, the temperature in ciliary body projection onto the ocular surface increased to 35.7°С (р = 0.002) for the challenged eyes and to 35.0°С (р=0.05) for the fellow eyes compared to eyes of intact rabbits (34.1°С). Purpose: To assess the histomorphology of the healthy fellow eye in rabbits with unilaterally induced non-infectious anterior and intermediate uveitis. Material and Methods: Seventeen Chinchilla rabbits (34 eyes; weight, 2.5-3.0 kg) were included in this study. Non-infectious anterior or intermediate uveitis was induced in the right eye of each rabbit, while the left was intact. Histomorphological studies of the fellow eyes were performed at various time points after challenge. Results: The fellow eyes showed normal histomorphology. Conclusion: A significant increase in the temperature in ciliary body projection onto the ocular surface to 35.0°С (р=0.05) for the fellow eyes compared to eyes of intact rabbits on day 1 of induced non-infectious anterior and intermediate uveitis in rabbits was not accompanied by any histomorphological or pathological changes, and was functional in nature.